Emulsion‐Induced Polymersomes Taming Tetrodotoxin for Prolonged Duration Local Anesthesia. Issue 1 (21st October 2022) - Li, Xiaosi; Li, Qi; Song, Shenghan; Stevens, Amy O.; Broemmel, Zach; He, Yi; Wesselmann, Ursula; Yaksh, Tony; Zhao, Chao
Abstract: Injectable local anesthetics that can provide a continuous nerve block approximating the duration of a pain state would be a life‐changing solution for patients experiencing post‐operative pain or chronic pain. Tetrodotoxin (TTX) is a site 1 sodium channel blocker that is extremely potent compared to clinically used local anesthetics. Challengingly, TTX doses are limited by its associated systemic toxicity, thus shortening the achievable duration of nerve blocks. Here, emulsion‐induced polymersomes (EIP) are explored as a drug delivery system to safely use TTX for local anesthesia. By emulsifying hyperbranched polyglycerol‐poly (propylene glycol)‐hyperbranched polyglycerol (HPG‐PPG‐HPG) in TTX aqueous solution, HPG‐PPG‐HPG self‐assembles into micrometer‐sized polymersomes within seconds. The formed polymersomes have microscopically visible internal aqueous pockets that encapsulate TTX with an encapsulation efficiency of up to 94%. Moreover, the polymersomes are structurally stable, enabling sustained TTX release. In vivo, the freshly prepared EIP/TTX formulation can be directly injected and increase the tolerated dose of TTX in Sprague–Dawley rats to 11.5 µg without causing any TTX‐related systemic toxicity. In the presence of the chemical penetration enhancer sodium octyl sulfate (SOS), a single perineural injection of EIP/TTX/SOS formulation produces a reliable sciatic nerve block for 22 days with minimal local toxicity. Abstract : Through a simple physical mixing process, tetrodotoxin and chemical penetration enhancers can be loaded into the polymersomes in seconds. The prepared formulation is ready for use without further processing. In rats, a single injection of this formulation blocks the sciatic nerve for ≈22 days without causing systemic toxicity of tetrodotoxin.